The undivided life : faculty of color bringing our whole selves to the academy - Alston, Judy A.; Tyson, Cynthia A., 1957- (Research, advocacy, collaboration, and empowerment mentoring series., 2024)
"Much of the research and writing on faculty of color and persistence in the Academy speaks to mentoring, recruitment, retention, job satisfaction, and the Imposter Syndrome. Yet, in spite of the significance (though we are small in numbers) and necessity of faculty of color in the Academy, there is no literature to describe or explain our experiences with regards to our holistic (body, mind, and spirit) existence and persistence in the Academy. Some questions that persist for faculty of color include: How do I continue to persist in the professoriate either in the tenure-track or as a tenured professor? How can I just be me and still be a successful professor? Do I have to check certain parts of me at the door or can I bring all of who I am into the Academy? How can I teach, research, and serve with my whole self and still have my work valued and accepted? Do I have to do safe research/work or can I do the work that I am passionate about? This collection of chapters are the personal stories from faculty of color who have persisted in the Academy despite the sometimes very steep climb"--